NMDA receptor subunit composition controls dendritogenesis of hippocampal neurons through CAMKII, CREB‐P, and H3K27ac. Issue 12 (11th May 2017) - Bustos, Fernando J.; Jury, Nur; Martinez, Pablo; Ampuero, Estibaliz; Campos, Matias; Abarzúa, Sebastian; Jaramillo, Karen; Ibing, Susanne; Mardones, Muriel D.; Haensgen, Henny; Kzhyshkowska, Julia; Tevy, Maria Florencia; et al.
Abstract : Dendrite arbor growth, or dendritogenesis, is choreographed by a diverse set of cues, including the NMDA receptor (NMDAR) subunits NR2A and NR2B. While NR1NR2B receptors are predominantly expressed in immature neurons and promote plasticity, NR1NR2A receptors are mainly expressed in mature neurons and induce circuit stability. How the different subunits regulate these processes is unclear, but this is likely related to the presence of their distinct C‐terminal sequences that couple different signaling proteins. Calcium‐calmodulin‐dependent protein kinase II (CaMKII) is an interesting candidate as this protein can be activated by calcium influx through NMDARs. CaMKII triggers a series of biochemical signaling cascades, involving the phosphorylation of diverse targets. Among them, the activation of cAMP response element‐binding protein (CREB‐P) pathway triggers a plasticity‐specific transcriptional program through unknown epigenetic mechanisms. Here, we found that dendritogenesis in hippocampal neurons is impaired by several well‐characterized constructs (i.e., NR2B‐RS/QD) and peptides (i.e., tatCN21) that specifically interfere with the recruitment and interaction of CaMKII with the NR2B C‐terminal domain. Interestingly, we found that transduction of NR2AΔIN, a mutant NR2A construct with increased interaction to CaMKII, reactivates dendritogenesis in mature hippocampal neurons in vitro and in vivo. To gain insights into the signaling and epigenetic mechanisms underlying NMDAR‐mediated dendritogenesis, we used immunofluorescence staining to detect CREB‐P and acetylated lysine 27 of histone H3 (H3K27ac), an activation‐associated histone tail mark. In contrast to control mature neurons, our data shows that activation of the NMDAR/CaMKII/ERK‐P/CREB‐P signaling axis in neurons expressing NR2AΔIN is not correlated with increased nuclear H3K27ac levels. Abstract : Dendrite arbor growth, or dendritogenesis, is choreographed by a diverse set of cues, including the NMDA receptor (NMDAR) subunits NR2A and NR2B. Here we found that dendritogenesis in hippocampal neurons is controlled by the interaction between NMDAR subunits and CaMKII in a developmental dependent manner.